Principles and algorithms of neurotic level anxiety disorders (anxiety-phobic, panic and generalized anxiety disorders) psychotherapy - T. A. Karavaeva; A. V. Vasileva; S. V. Poltorak (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Article presents modern approaches to the psychotherapy of neurotic level anxiety disorders with the use of the evidence based outcome-oriented research. It considers the main targets, steps and contraindications for psychotherapy. Algorithms of the main psychotherapeutic methods used for the treatment of patients with neurotic level anxiety disorders (CBT, interpersonal and personality-oriented (reconstructive) psychotherapy) are described. The article reviews and appraises the strength and weight of the research findings of the definite methods effectiveness and strength of the recommendations.